Transmitting Local Wisdom Culture by Applying Local Wisdom-Based Comic Strips in Teaching Writing - Puput Zuli Ekorini (Dharma Pendidikan, 2020)
The present paper aims to know whether there is any influence of using local wisdom-based comic strips in teaching writing for the junior high school students. Local wisdom-based comic strips is a developed comic strips that contain local wisdom as the knowledge of the local people which is inherited hereditary. Creating the local wisdom-based comic strips and applying them as media to teach writing aims to facilitate the students and teacher to do the teaching and learning process. Besides, they also can create the education which can provide the meaning for local people’s life. In other words education can be the spirit which colors the local people’s life. The research design is quasi experimental with two group as experimental group and control group which uses t-test to analyze the data and compares the results. The researcher used a test in form of writing test as the instrument of getting the data. There were 70 students which were taken as sample from a junior high school in Nganjuk which are separated into two groups of experimental and control. The research result was shown by the mean score of experimental class is 78.19. It also can be seen that the value of Sig. (2-tailed) is 0.000 which means that the value of Sig. (2-tailed) < 0.05. So the alternatives hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. The conclusion is the use of local wisdom-based comic strips has a significant influence to the students writing skill.